THE EFFECT OF BAIT TYPE ON BOTTOM LONGLINE FISHING CATCH IN EKAS BAY - Lalu Samsul Rizal; Rian Permadi Bohari; Lalu Achmad Tan Tilar Wangsajati Sukmaring Kalih (Universitas Mataram, 2024)
Bottom longlines are operated using different types of bait in Batu Nampar Selatan Village. This research aims to reveal the influence of different types of basic longline bait on catches and economic profits obtained by fishermen in Ekas Bay. The method used in this research is an experimental survey, by comparing the results of 3 different types of bait in-situ. T-test analysis or t-test is used to prove that there are differences in the bait caught. R/C ratio analysis is used to calculate the economic benefits of basic longline catches. The total catch was 185 fish weighing 42.8 kg. The results of the T-test analysis obtained a significant value of 0.924 or a significant value > 0.05, so the hypothesis (H0) was accepted. This means that different types of bait do not have a real influence on bottom longline catches in Ekas Bay. The results of the R/C ratio analysis from the use of 3 types of bait, namely, anchovy bait (Stolephorus indicus) 8.6; squid bait (Loligo sp) 9.5; combination bait of anchovies (S. indicus) and squid (Loligo sp.) 8.84. It can be concluded that the three types of bait are profitable and worth continuing